Research Paper: Brain CT Scan Findings in Patients Admitted to the Poisoning ICU of Baharloo Hospital, Tehran, Iran - Behnoush, Behnam; Gahramani, Mahvash; Taghaddosinejad, Fakhredin; Okazi, Arash (International Journal of Medical Toxicology and Forensic Medicine, 2017)
Background: Timely and correct diagnosis of poisoning is an important part of the management of poisoned patients. This study aimed to investigate the abnormal findings of brain CT scans of patients with drug overdose poisoning. Methods: A retrospective cross-sectional study was conducted on patients with poisoning admitted to Baharloo Hospital, Tehran, Iran during 2015. Moreover, they underwent radiological assessment as a result of their decreased level of consciousness. For the purpose of the study, we examined patients’ Computerized Tomography (CT) scan reports. The collected data were analyzed with SPSS 16. Frequency and percentage frequency were calculated for qualitative variables, and mean and standard deviation were calculated for the quantitative variables. Results: Overall, 191 patients admitted with poisoning were evaluated. Of them, 119(62.3%) had normal brain CT scans and the remaining had pathologic findings. The most common pathologic findings in the brain CT scans comprised cerebral edema (24.6%) followed by infarction (5.2%). The least common pathologic finding was cerebral herniation (0.5%). This pattern was similar in both genders and in different subtypes of poisonings, with the exception of poisoning with cardio-respiratory drugs. The most common finding in the latter type of poisoning was herniation. In cases of simultaneous head trauma, the most common pathological brain CT scan findings were cerebral edema and hemorrhage. Conclusion: The radiological assessment of the brain following poisoning and decreased level of consciousness can help in the diagnostic evaluation of patients. It can be a life-saving measure, through timely detection of the type of poisoning and brain damage.